Sirolimus use in liver transplant recipients with hepatocellular carcinoma: a randomized, multicenter, open-label phase 3 trial - Geissler, Edward K.; Schnitzbauer, Andreas A.; Zülke, Carl; Lamby, Philipp E.; Proneth, Andrea; Duvoux, Christophe; Burra, Patrizia; Jauch, Karl-Walter; Rentsch, Markus; Ganten, Tom M.; Schmidt, Jan; Settmacher, Utz; et al. (Transplantation, 2016)
We investigated whether sirolimus-based immunosuppression improves outcomes in liver transplantation (LTx) candidates with hepatocellular carcinoma (HCC)., In a large prospective randomized open-label international trial, liver transplant recipients for HCC were randomized to receive non-mTOR-inhibitor-based-treatment or mTOR-inhibitor-based-treatment. Results indicate overall sirolimus does not improve long-term recurrence-free survival beyond 5 years while a benefit was seen in low-risk patients. Supplemental digital content is available in the text.
Published online: 2015 Dec 16
Gesehen am 27.05.2020